La mosquée au service des objectifs économiques des programmes d’alphabétisation des adultes au Maroc - Ibourk, Aomar; Elmakhloufi, Kabir (International review of education, 2025)
The mosque at the service of the economic objectives of adult literacy programmes in Morocco – In Morocco, in addition to their religious missions, mosques play a role in adult education and training, thereby promoting the integration of adult learners. This article develops an economic index to assess this integration. It uses ad hoc data collected by monitoring a cohort of 351 learners over five and a half years. Promising results show significant progress in this area, with 18.87% of women achieving their economic goals. The study identifies three dimensions to this integration. The first is linked to the internal and external environmental context of the learning operation. The second is linked to the learners’ socio-demographic and economic characteristics. The third is linked to the socio-demographic characteristics of the supervisors. This study is limited by the lack of assessment of the reading and writing skills of neo-literates. A target of sixty correct words per minute is recommended as an objective measure of these skills.